Stuttering: A Disorder of Energy Supply to Neurons? - Alm, Per A. (Frontiers in Human Neuroscience, 2021)
Stuttering is a disorder characterized by intermittent loss of volitional control of the speech movements. This Hypothesis and Theory article focuses on the proposal that stuttering may be related to an impairment of the energy supply to neurons. Findings from electroencephalography (EEG), brain imaging, genetics, and biochemistry are reviewed. Analyses of the EEG spectra at rest have repeatedly reported reduced power in the beta band, which is compatible with indications of reduced metabolism. Studies of the absolute level of regional cerebral blood flow (rCBF) show conflicting findings, with two studies reporting reduced rCBF in the frontal lobe, and two studies, based on a different method, reporting no group differences. This contradiction has not yet been resolved. The pattern of reduction in the studies reporting reduced rCBF corresponds to the regional pattern of the glycolytic index (GI, Vaishnavi et al., 2010). High regional GI indicates high reliance on non-oxidative metabolism, i.e., glycolysis. Further, variants of the gene ARNT2 have been associated with stuttering. This gene is primarily expressed in the brain with a pattern roughly corresponding to the pattern of regional GI. A central function of the ARNT2 protein is to act as one part of a sensor system indicating low levels of oxygen in brain tissue, and to activate appropriate responses, including activation of glycolysis. Further, it has been established that genes related to the functions of the lysosomes are implicated in some cases of stuttering. It is possible that these gene variants result in a reduced peak rate of energy supply to neurons. Lastly, there are indications of interactions between the metabolic system and the dopamine system: For example, acute hypoxia results in an elevated tonic level of dopamine in the synapses – will mild chronic limitations of energy supply also result in elevated levels of dopamine? The indications of such interaction effects suggest that the metabolic theory of stuttering should be explored in parallel with the exploration of the dopaminergic theory. It is preliminary hypothesized that stuttering can be related to an impairment of cerebral glycolysis.